2023
DOI: 10.1002/fft2.284
|View full text |Cite
|
Sign up to set email alerts
|

Miquelianin, a main functional flavonoid of lotus leaf, induces thermogenic signature via p38‐PINK1‐PARKIN‐mediated mitophagy and mimicking NRF2 signaling during brown adipocyte differentiation

Abstract: Adipocytes thermogenesis is an important mechanism for increasing energy expenditure. Here, screening of thermogenic activators (Sirt1 and Ucp1) investigated in C3H10T1/2 cells revealed ethanol extract of lotus leaf (LLE) may exert higher activity compared with that of the other 11 ingredients. UPLC‐MS/MS analysis showed that miquelianin was identified as the main flavonoid compounds in LLE (12.8%) and therefore deserves further investigation. The results in C3H10T1/2 cells revealed miquelianin promoted lipoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Miquelianin (quercetin 3- O -glucuronide) is a primary functional flavonoid found in lotus leaves. It possesses anti-inflammatory, anti-atherogenic, and antioxidant properties, and by dissipating energy, it may be utilized as a new food raw material or nutritional supplement in weight loss products [ 72 ]. This flavonoid is derived from Hypericum perforatum L., and in vivo, pharmacological studies have demonstrated its antidepressant properties [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…Miquelianin (quercetin 3- O -glucuronide) is a primary functional flavonoid found in lotus leaves. It possesses anti-inflammatory, anti-atherogenic, and antioxidant properties, and by dissipating energy, it may be utilized as a new food raw material or nutritional supplement in weight loss products [ 72 ]. This flavonoid is derived from Hypericum perforatum L., and in vivo, pharmacological studies have demonstrated its antidepressant properties [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…In ovariectomized mice, quercitrin decreased the expression of p-INK, p-ERK, and p-p38 to blunt the MAPK signaling pathways [48]. Similarly, the crucial flavonoid from lotus leaf can mediate brown-adipocyte differentiation and thermogenic via inhibiting the p38 MAPK signal pathway [49]. Chung et al [50] found that quercetin could markedly inhibit the IgE-antigen complex that stimulates phosphorylation of the p38, ERK, and JNK proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Determination of NADH content, NAD + content and NAD + / NADH ratio A NAD + /NADH Quantification Kit (Beyotime) was used for the determination of NADH content, NAD + content and NAD + /NADH ratio according to our previous report. 11…”
Section: Mitochondrial Stainingmentioning
confidence: 99%